Peran Kegiatan Rekreasioal Berbasis Fun Games dalam Meningkatkan Kepuasan dan Kebahagiaan Warga Binaan Pemasyarakatan Lapas Kelas 1 Makassar - Basti Tetteng; Ichwan Sabil; Sil Mutadayana; Mutiara Putri Ananda (Lembaga Pengembangan Kinerja Dosen, 2025)
The Professional Work Lecture (KKP) at the Makassar Class I Prison aims to support the process of fostering Correctional Assisted Citizens (WBP) through recreational activities based on fun games. This program was implemented in response to the condition of WBPs who often experience boredom, psychological stress, and limitations in positive activities during the coaching period. This study uses a descriptive approach with data collection techniques in the form of questionnaires, observations, and interviews involving 30 WBPs, to identify needs and evaluate the impact of the implementation of activities. Fun games activities are carried out through several stages, namely planning, preparation, implementation, and evaluation, by adjusting the conditions and rules that apply in the prison environment. The results of the implementation show that this activity is able to create a more positive atmosphere, increase a sense of togetherness, and help WBP in expressing and managing emotions in a healthier way. The results of the post-activity survey showed that 19 WBPs stated that they were very satisfied and 18 WBPs felt very happy after participating in fun games. Thus, fun games activities have proven to be effective as a coaching strategy that supports the improvement of the psychological welfare of WBP and can be used as an alternative to non-formal coaching programs in correctional institutions.